Breeding and evaluation of Pleurotus giganteus (Berk.) Karunarathna & K.D. hyde hybrids via intraspecific mating - Ha, Kwan Yun; Chua, Su Boon; Tan, Yee Shin; Vikineswary Sabaratnam, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Pleurotus giganteus, the giant oyster mushroom is gaining popularity as a gourmet mushroom. The cultivation of this mushroom in Malaysia, however, is facing challenges such as malformed pinhead formation and low yield resulting in heavy economic losses for farmers. The aim of this study was to generate new hybrids of P. giganteus with higher yield for commercialisation in Malaysia. The commercial strain of P. giganteus (China) (KLU-M1227) and a wild strain from Malaysia (KLU-M1391) were subjected to intraspecific breeding. A total of 16 hybrids were obtained from 56 combinations. All the parents and hybrids were subjected to linear growth assessment. The hybrids were clustered into slow-growing (growth rate < 0.29 cm/day) and fast-growing (growth rate in 0.30 cm/day) types. The parents and three hybrids (IH15, IH17 and IH32) that were the least susceptible to Trichoderma sp. were then cultivated using soil-casing method. This method was able to solve long, coiling stipe formation of P. giganteus. The parent and hybrid strains showed variation in the number of days for pinhead formation and number of fruiting bodies formed. The hybrid with the highest yield (IH32) had a 32% higher biological efficiency compared to both the parents. Inter simple sequence repeats (ISSR) amplifications were carried out to confirm the generation of the hybrids. Hybrids IH17 and IH32 contained the genetic materials inherited from both parents while hybrid IH15 shared high amount of genetic materials from one parent.